Effect of Seed Coating on Storability of Barley (Hordeum vulgare L.) Seeds: Seed Coating Impact on Barley Storability - Walia, Parul; Dhiman, KC; Kanwar, Rajesh; Kapila, RK (Journal of Cereal Research, 2025)
The present experiment was carried out to study the effect of different seed coating treatments on seed quality parameters during storage in barley. The seeds of barley variety HBL - 276 also known as “Harit” were treated with nine different seed coating treatment combinations consisting of polymer, fungicides, insecticide and bio-fungicides. Untreated seeds served as control. Both treated and untreated seeds were stored in Completely Randomized Design (CRD) with three replications for twelve months after packing in interwoven HDPE bags. The observations on different seed quality parameters were recorded at bi-monthly intervals for twelve months (March 2022 - March 2023). The results of the storage experiment showed a decline in all the seed quality parameters irrespective of various seed coating treatments with the advancement in storage period. The treatment T6 - polymer + vitavax power (containing thiram 37.5% and carboxin 37.5%) @ 2.0 g/kg of seed recorded significantly highest seed quality parameters viz., germination percentage - final count (87.00%), rate of germination (79.50), seedling length (38.85 cm), dry matter of seedling (18.95 mg), vigour index - I (3380.24), vigour index - II (1648.36) and field emergence (74.00%) which was statistically at par with T4 - polymer + treat (tebuconazole) @ 1.0 g/kg seed and T5 - vitavax power (containing thiram 37.5% and carboxin 37.5%) @ 2.0 g/kg seed after 12 months of storage period. Hence, it can be inferred that seeds treated with polymer coating @ 3.0 ml per kg of seed + vitavax power (containing thiram 37.5% and carboxin 37.5%) @ 2.0 g/kg of seed or with polymer @ 3.0 ml per kg of seed + treat (tebuconazole) @ 1.0 g/kg seed or with vitavax power (containing thiram 37.5% and carboxin 37.5%) @ 2.0 g/kg seed can be used for maintaining better storability of barley seed up to 12 months.